Monitoring Systems for Counting People Based on Wireless Multimedia Sensor Network - Rantelobo, Kalvein; Sampeallo, Agusthinus; Mandala, J. F.; Lami, H. F. J.; Bernandus, B.; Rantelinggi, P. H.; Sastra, N. P. (Universitas Nusa Cendana, 2025)
The visual sensor used in the Wireless Sensor Multimedia Networks (WSMN) in this work aims to monitor and calculate the number of people passing through a room. The contribution of this paper is the use of Raspberry Pi 3 devices that are connected to the internet using Internet-of-Thing (IoT) technology. The proposed scheme can be implemented in the actual environment. From the test results, the system has distinguished people entering and leaving the room by doing image processing using background subtraction, morphological transformation method, and calculating the contour area of the image. The results of image processing can calculate the number of people in the room, and the system can send it to the web server. Subsequently, this paper discussed the energy consumption used by the WSMN and explained test parameters.